2018
DOI: 10.1080/00140139.2018.1508756
|View full text |Cite
|
Sign up to set email alerts
|

The role of peripheral vision in vertical road sign identification and discrimination

Abstract: The role of peripheral vision in road sign identification and discrimination was investigated in two studies. Peripheral vision plays an important role in road signs perception due to their lateral positioning. In the first study 20 participants identified road signs presented at five levels of horizontal eccentricity (1.1°-12.4°), and two levels of vertical eccentricity (0°-2.5°). In the second study road sign discrimination was tested in a same-different discrimination task. The first study showed that a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…This data is even more significant when considering that the participants wore an eye tracker device, drove an unfamiliar car and knew that their driving behaviour was being studied. This frequency, however, does not take into account a possible involvement of peripheral vision in road sign detection and identification (Costa, Bonetti, Vignali, Lantieri, & Simone, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This data is even more significant when considering that the participants wore an eye tracker device, drove an unfamiliar car and knew that their driving behaviour was being studied. This frequency, however, does not take into account a possible involvement of peripheral vision in road sign detection and identification (Costa, Bonetti, Vignali, Lantieri, & Simone, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In real-world driving situations, where traffic patterns change in a highly dynamic way, quick fixations may occur, as in the case of this study [50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Velichkovsky, Domhoefer, Pannasch, & Unema (2000), for example, reported that fixations around 60 ms made up around 7% of all fixations during a simulated driving task. Short fixations in a driving task have been also reported by Sodhi et al (2002), who found a modal value for on-road fixation duration of 20 ms, and a modal interval for off-road fixations of 40-60 ms. Lantieri et al (2015) and Costa, Bonetti, et al (2018), found that in real traffic situations, due to the high dynamical context of road driving, mean fixation duration is much lower than in other contexts and experimental settings. In a real driving task, as in this study, car movements and the complex optical flow of the dynamical visual scene could cause very rapid fixations.…”
Section: Number Of Fixations and Fixation Durationmentioning
confidence: 90%
“…The main applications of mobile eye tracking studies in driving behaviour are steering, braking, multitasking, city driving and driving learning (Land & Tatler, 2009). In addition, eye tracking was also used to study drivers' detection, perception and acknowledgment of different road elements, to optimize the driving strategy and prevent accidents (Bongiorno, Bosurgi, Pellegrino, & Sollazzo, 2017;Costa, Simone, Vignali, Lantieri, Bucchi, & Dondi, 2014;Costa, Bonetti, Vignali, Lantieri, & Simone, 2018;Costa, Simone, Vignali, Lantieri, & Palena, 2018;Inman, 2012;Kapitaniak et al, 2015;Lantieri et al, 2015;Mantuano, Bernardi, & Rupi, 2017).…”
Section: Drivers' Eye-movements Approaching Pedestrian Crossingsmentioning
confidence: 99%
See 1 more Smart Citation